The winning percentage in congkak using a randomised strategy - Chuei, Yee Chen; Ismail, Shahrina; Lim, Fong Peng; Yow, Kai Siong (Prince of Songkla University, 2022)
Congkak is a traditional counting game played in Southeast Asia including Malaysia, Singapore, Brunei and Indonesia. To start a game, a board that has 16 holes together with 98 marbles are required. Each player controls a set of seven holes and own a store. The winner of the game is the player who captured more marbles into the store at the end of the game. Note that the firstmove advantage exists in chess; we investigate if the first-move advantage holds in congkak also. We model the route for each player in congkak using a directed graph and adopt these graph representations in our programs, to compute the winning percentage of each player. We focus on games between novices, hence a randomised strategy is used in our algorithm. We present the first experimental results for 100,000 games between novices in congkak. We also suggest some questions for future research in this area.